Evaluation of the Effects of Menstrual Cycle on Postural Stability in Active Young Women - Güler, Özkan; Dıedhıou, Azize; Şahin, Fatma Neşe; Ersöz, Gülfem (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
Menstruation is considered as the primary biological factor between men and women. Many studies indicate that the prevalence of injury is higher in female athletes than in male athletes. In the previous studies, an association between postural stability and injury rate has been reported. The purpose of this study is to evaluate the stability of physically active women during different phases of the menstrual cycle. Young women who exercised regularly and had a regular menstrual cycle (n = 19, age: 20.4 +/- 1.2 years; height: 164.78 +/- 4.66 cm; body weight: 54.63 +/- 3.41; BMI: 20.11 +/- 0.97 menstruation: 28.47 +/- 1.26) participated in the study. The Menstrual cycle is divided into three different phases. The stability was measured in the early menstrual phase, the follicular phase, and the middle of the luteal phase. Postural stability index (PSI) and Limit of stability (LOS), tests were performed with the Biodex SD System (Biodex, Shirley, NY). During the ovulation phase, according to LOS test results (p=0.016), a statistical difference was found between the three phases. According to this result, LOS values decreased in the ovulation phase compared to other phases. No difference was determined between anterior-posterior oscillation, mediolateral oscillation, and postural stability index scores and menstrual phases (p=0.34). It is observed that stability in women who perform active sports is affected by different menstrual phases. It can be said that the deterioration in stability is caused by the increase in sex hormones muscle and joint laxity during the ovulation phase.
Keywords: Balance; Mensturation; Postural sway